Maintenance problems of office building services in Merlin Tower - Yong, Yann Shian (2010)
Defect or damage is hard to avoid in a building. If a building is not under a well maintenance a lot of problems such as leakage and crack will happen in the building. Hence maintenance is very important for a building especially for public building such as office building. Maintenance helps to reduce the defects or damage happen and provide a pleasant environment to the users inside the office building. According to maintenance department and tenants of Merlin Tower, there are faced some problem in maintenance such as air condition system, electrical system, plumbing system and security system. There are two objectives for this study which are to identify and analyse the maintenance problems of building services inside Merlin Tower office building and to find out the maintenance works to solve the maintenance problems of building services in Merlin Tower office building. Maintenance problems of building services was identified through questionnaires which constructed with likert scale question. 30 sets of questionnaire were analysed and it was from the maintenance department and tenants of Merlin Tower. Mean score method are applied in the analysis by SPSS. Whilst maintenance method of office building was identified through interviews conducted to Merlin Tower and the comparison buildings which are Public Bank Tower, Menara Pelangi and Menara Ansar. Content analysis was used to analyse the data from interviews. Throughout the research, air condition system and electrical system are the building services that often facing maintenance problem in Merlin Tower. Maintenance department of Merlin Tower should pay more attention on preventive maintenance, replacement work, establish proper maintenance schedule and checklist, have spare part inventory, material consideration and keep the facilities histories. All these method can help Merlin Tower have an effective maintenance and reduce the defects that happen in building services.